Yeast nuclear envelope proteins cross react with an antibody against mammalian pore complex proteins (The Rockefeller University Press, 1989)
We have used a monoclonal antibody raised against rat liver nuclear proteins to study two cross-reactive proteins in the yeast nucleus. In rat liver, this monoclonal antibody, mAb 414, binds to nuclear pore complex proteins, including one of molecular weight 62,000 (Davis, L. I., and G. Blobel. 1987. Proc. Natl. Acad. Sci. USA. 84:7552-7556). In yeast, mAb 414 cross reacts by immunoblotting with two proteins that have apparent molecular weights of 110,000 and 95,000, and are termed p110 and p95, respectively. Examination of subcellular fractions by immunoblotting shows that both p110 and p95 are located exclusively in the nuclear fraction. The mAb 414 immunoprecipitates several proteins from a crude yeast cell extract, including p110, p95, and a approximately 55-kD protein. Immunoprecipitation from subcellular fractions yields only p110 and p95 from purified nuclei, whereas the approximately 55-kD protein is immunoprecipitated from the soluble fraction. Digestion of purified nuclei with DNase to produce nuclear envelopes releases some of p110, but the majority of p110 is solubilized only after treatment of envelopes with 1 M NaCl. Immunofluorescence localization using yeast cells and isolated nuclei shows a punctate and patchy staining pattern of the nucleus. Confocal laser scanning immunofluorescence microscopy resolves the punctate and patchy staining pattern better and shows regions of fluorescence at the nuclear envelope. Postembedding immunogold electron microscopy using purified nuclei and mAb 414 shows colloidal gold decoration of the yeast nuclear envelope, but resolves pore complexes too poorly to achieve further ultrastructural localization. Immunogold labeling of nuclei followed by embedding suggests decoration of pore complexes. Thus, p110 and/or p95 are localized to the nuclear envelope in yeast, and may be components of the nuclear pore complex.